Efficacy of recreational football on bone health, body composition, and physical functioning in men with prostate cancer undergoing androgen deprivation therapy: 32-week follow-up of the FC prostate randomised controlled trial. Issue 4 (April 2016) - Uth, J.; Hornstrup, T.; Christensen, J.; Christensen, K.; Jørgensen, N.; Schmidt, J.; Brasso, K.; Jakobsen, M.; Sundstrup, E.; Andersen, L.; Rørth, M.; Midtgaard, J.; et al.
Abstract Summary Androgen deprivation therapy (ADT) for prostate cancer (PCa) impairs musculoskeletal health. We evaluated the efficacy of 32-week football training on bone mineral density (BMD) and physical functioning in men undergoing ADT for PCa. Football training improved the femoral shaft and total hip BMD and physical functioning parameters compared to control. Introduction ADT is a mainstay in PCa management. Side effects include decreased bone and muscle strength and increased fracture rates. The purpose of the present study was to evaluate the effects of 32 weeks of football training on BMD, bone turnover markers (BTMs), body composition, and physical functioning in men with PCa undergoing ADT. Methods Men receiving ADT >6 months (n  = 57) were randomly allocated to a football training group (FTG) (n  = 29) practising 2–3 times per week for 45–60 min or to a standard care control group (CON) (n  = 28) for 32 weeks. Outcomes were total hip, femoral shaft, femoral neck and lumbar spine (L2-L4) BMD and systemic BTMs (procollagen type 1 amino-terminal propeptide, osteocalcin, C-terminal telopeptide of type 1 collagen). Additionally, physical functioning (postural balance, jump height, repeated chair rise, stair climbing) was evaluated. Results Thirty-two-week follow-up measures were obtained for FTG (n  = 21) and for CON (n  = 20), respectively. Analysis of mean changes from baseline to 32 weeks showed significant differences between FTG and CON in right (0.015 g/cm2 ) and left (0.017 g/cm2 ) total hip and in right (0.018 g/cm2 ) and left (0.024 g/cm2 ) femoral shaft BMD, jump height (1.7 cm) and stair climbing (−0.21 s) all in favour of FTG (p  < 0.05). No other significant between-group differences were observed. Conclusions Compared to standard care, 32 weeks of football training improved BMD at clinically important femoral sites and parameters of physical functioning in men undergoing ADT for PCa.